Pengaruh Rasio Likuiditas,Profitabilitas, Dan Leverage Terhadap Financial Distress Pada Perusahaan Tekstil Dan Garment Yang Terdaftar di BEI Periode 2017-2022 - Athia Zainun Faqiha; Solihin Sidik (STIE AMKOP, 2023)
This research was made with the aim of knowing, analyzing, and identifying the effect of liquidity ratios, profitability, and leverage on financial distress in textile and garment companies listed on the Indonesia Stock Exchange. This type of research is quantitative using secondary data obtained from annual financial report data for textile and garment companies listed on the Indonesia Stock Exchange (IDX) from 2017-2022. Sampling was carried out by purposive sampling method with a total population in this study, namely as many as 22 textile and garment companies, so that the total sample in this research was 36 data, from 6 companies for 6 years.Based on the results of the t test and F test in this study, this study obtained the following results: liquidity ratios have no effect on financial distress, profitability and leverage have a significant positive effect on financial distress, and liquidity ratios, profitability and leverage have a simultaneous effect on financial distress.